TASK-BASED VOCABULARY DEVELOPMENT STRATEGIES - Kalayo Hasibuan; Ahmad Gozali; Diva Cahyani Rezky; Fadilla Refahtunisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocabulary mastery is one of the essential components in English language learning because it supports students’ ability to communicate effectively. However, many students still experience difficulties in learning and using English vocabulary due to traditional teaching methods that emphasize memorization rather than meaningful communication. This article discusses Task-Based Vocabulary Development Strategies as an effective approach for improving vocabulary acquisition among English as a Foreign Language (EFL) learners. The study employed a qualitative descriptive library research design by analyzing theories, books, journal articles, and previous studies related to Task-Based Language Teaching (TBLT) and vocabulary instruction published between 2000 and 2025. The findings indicate that task-based activities such as information-gap tasks, role plays, problem-solving activities, story completion tasks, and vocabulary games significantly improve vocabulary retention, learner motivation, classroom interaction, and communicative competence. In addition, task-based learning encourages students to use vocabulary actively in meaningful communication contexts. The study concludes that task-based vocabulary learning is highly beneficial for EFL classrooms because it creates interactive and student-centered learning environments. Therefore, teachers are encouraged to implement communicative tasks to improve students’ vocabulary mastery and engagement in English learning. Keywords: Task-Based Learning, Vocabulary Development, EFL, Language Teaching, Communicative Learning